Distribution and clinical manifestations of Cryptosporidium species and subtypes in HIV/AIDS patients in Ethiopia. - Haileeyesus Adamu; Beyene Petros; Guoqing Zhang; Hailu Kassa; Said Amer; Jianbin Ye; Yaoyu Feng; Lihua Xiao (Public Library of Science (PLoS), 2014)
BACKGROUND: Cryptosporidiosis is an important cause for chronic diarrhea and death in HIV/AIDS patients. Among common Cryptosporidium species in humans, C. parvum is responsible for most zoonotic infections in industrialized nations. Nevertheless, the clinical significance of C. parvum and role of zoonotic transmission in cryptosporidiosis epidemiology in developing countries remain unclear. METHODOLOGY/PRINCIPAL FINDINGS: In this cross-sectional study, 520 HIV/AIDS patients were examined for Cryptosporidium presence in stool samples using genotyping and subtyping techniques. Altogether, 140 (26.9%) patients were positive for Cryptosporidium spp. by PCR-RFLP analysis of the small subunit rRNA gene, belonging to C. parvum (92 patients), C. hominis (25 patients), C. viatorum (10 patients), C. felis (5 patients), C. meleagridis (3 patients), C. canis (2 patients), C. xiaoi (2 patients), and mixture of C. parvum and C. hominis (1 patient). Sequence analyses of the 60 kDa glycoprotein gene revealed a high genetic diversity within the 82 C. parvum and 19 C. hominis specimens subtyped, including C. parvum zoonotic subtype families IIa (71) and IId (5) and anthroponotic subtype families IIc (2), IIb (1), IIe (1) and If-like (2), and C. hominis subtype families Id (13), Ie (5), and Ib (1). Overall, Cryptosporidium infection was associated with the occurrence of diarrhea and vomiting. Diarrhea was attributable mostly to C. parvum subtype family IIa and C. hominis, whereas vomiting was largely attributable to C. hominis and rare Cryptosporidium species. Calf contact was identified as a significant risk factor for infection with Cryptosporidium spp., especially C. parvum subtype family IIa. CONCLUSIONS/SIGNIFICANCE: Results of the study indicate that C. parvum is a major cause of cryptosporidiosis in HIV-positive patients and zoonotic transmission is important in cryptosporidiosis epidemiology in Ethiopia. In addition, they confirm that different Cryptosporidium species and subtypes are linked to different clinical manifestations.